Предмет: Алгебра,
автор: kozlovakira823
Упростите выражение (4a-2b) (3a+b²)-(6a-b²)(2a+2b) и найдите значение при а= - 1/3 и b= 0,5.
Ответы
Автор ответа:
1
Объяснение:
a= -1/3 ; b=0,5
(4а-2b)(3a+b²)-(6a-b²)(2a+2b)=
=12a²+4ab²-6ab-2b³-(12a²+12ab-2ab²-2b³)=
= 12a²+4ab²-6ab-2b³-12a²-12ab+2ab²+2b³=
=6ab²-18ab=6ab(b-3)=6•(-1/3)•0,5•(0,5-3)=
= -1•(-2,5)=2,5
Похожие вопросы
Предмет: Литература,
автор: arsruslanov37
Предмет: География,
автор: tamaraworozbyt
Предмет: Математика,
автор: evvii
Предмет: Алгебра,
автор: Arina202020
Предмет: Математика,
автор: brotheroptop